(untitled) (Journal of University of Babylon for Engineering Sciences, 2025)
In this study, the effect of the addition of low-density polyethylene (LDPE) at different weight percentages (0, 10, 20, 30, 40, and 50) % The thermal and mechanical features of the high-density polyethylene (HDPE) were examined. The HDPE/LDPE combinations were prepared by using a twin-screw extruder. The mechanical properties (tensile properties, impact strength, hardness) , thermal properties using differential scanning calorimetry (DSC) were investigated , the Fourier Transform Infrared Spectroscopy (FTIR) test was also conducted to examine whether a chemical bond was formed in the combination or not And Surface morphological alterations of HDPE, LDPE, and HDPE/LDPE were analyzed using scanning electron microscopy (SEM). The results indicate a reduction in tensile strength and Young’s modulus, accompanied by an increase in elongation at rupture. The impact strength was improved by the LDPE addition, while the Shore D hardness decreased. The DSC results indicate that the addition of LDPE reduced both the melting point and the degree of crystallinity. The FTIR indicated that there is a physical interaction between the two polymers. The SEM test revealed that the combination of two phases of LDPE exhibited superior softness compared to the LDPE sample, in addition to the presence of the phases.